Alkaline earth metal ion doped titanium-based phosphate composite material as well as preparation method and application thereof
The lattice structure of the titanium-based phosphate material is stabilized by doping alkaline earth metal ions, and the battery life and reversible capacity problems caused by exchange of potassium ions and sodium ions are solved, achieving higher cycling stability and service life.
Patent Information
- Application Number
- CN202510131761.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2045-02-06
AI Technical Summary
When existing titanium-based phosphate materials are used in sodium ion batteries, the exchange between potassium ions and sodium ions leads to changes in the material structure and composition, affecting the battery's life and reversible capacity.
The lattice structure of the titanium-based phosphate material is stabilized by doping alkaline earth metal ions such as magnesium and calcium, and the exchange of K-Na ions is avoided. Doping amount and process parameters are optimized to improve the electrochemical properties of the material.
It significantly improves the cycle stability and service life of sodium ion batteries, enhances the overall stability and electrical performance of the material, reduces internal resistance, and improves the power performance of the battery.
Smart Images

Figure CN119560544A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to an alkaline earth metal ion-doped titanium-based phosphate composite material, and a preparation method and application thereof. Background Art
[0002] As a sodium ion electrode material, sodium titanium phosphate has excellent structural and thermal stability. However, its extremely low electronic conductivity and insufficiently spacious ion diffusion channels severely limit its application in sodium ion batteries. Among various titanium-based phosphate materials, KTiOPO4 has a larger cross-cavity and the lowest potential of KTiOPO4, which is 1.23V. It has great potential in achieving faster ion dynamics and lower cycle strain in sodium ion batteries. However, when KTiOPO4 is used as a sodium ion negative electrode material, potassium ions will be replaced by sodium ions through ion exchange during the charge and discharge cycle. This ion exchange will cause changes in the composition and structure of the material, which will affect the battery life and reversible capacity.
[0003] Therefore, it is still necessary to develop a titanium-based phosphate material with long service life and high reversible capacity. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an alkaline earth metal ion-doped titanium-based phosphate composite material and its preparation method and application, and improves the electrochemical performance of titanium-based phosphate materials in secondary sodium ion batteries from multiple angles and dimensions through the strategy of alkaline earth metal ion doping. Through the type and doping amount of alkaline earth metal ions and the optimization of process parameters, the lattice structure of titanium-based phosphate materials is stabilized, the exchange of K-Na ions is effectively avoided, and the performance of sodium ion batteries is significantly improved.
[0005] The first object of the present invention is to provide an alkaline earth metal ion-doped titanium-based phosphate composite material, wherein the chemical formula of the alkaline earth metal ion-doped titanium-based phosphate composite material is K x M y TiOPO4 / C, M is selected from one or more of beryllium, magnesium, calcium, strontium and barium, 0.8≤x≤0.95, 0.001≤y≤0.1, and the values of x and y satisfy the charge balance of the chemical formula.
[0006] In one embodiment of the present invention, the M is selected from magnesium and / or calcium.
[0007] In one embodiment of the present invention, the chemical formula of the alkaline earth metal ion-doped titanium-based phosphate composite material is K 0.9 Ca 0.05 TiOPO4 and / or K 0.9 Mg 0.05 TiOPO4.
[0008] In one embodiment of the present invention, the K x M y The mass ratio of TiOPO4 and C is (0.7-0.99):(0.01-0.3).
[0009] The second object of the present invention is to provide a method for preparing the alkaline earth metal ion-doped titanium-based phosphate composite material, comprising the following steps: uniformly mixing a K source, an M source, a Ti source, a P source and a carbon source by wet ball milling, and obtaining the alkaline earth metal ion-doped titanium-based phosphate composite material by drying, sintering, cooling and crushing.
[0010] In one embodiment of the present invention, the K source is selected from one or more of potassium hydroxide, potassium carbonate, potassium sulfate, potassium dihydrogen phosphate and potassium acetate; And / or, the M source is selected from one or more of a beryllium source, a magnesium source, a calcium source, a strontium source and a barium source; and / or, the Ti source is selected from one or more of titanyl sulfate, titanium dioxide, tetrabutyl titanate and titanium tetrachloride; And / or, the P source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphorus pentoxide and potassium dihydrogen phosphate; And / or, the carbon source is selected from one or more of acetylene black, graphite, conductive carbon black, sucrose and glucose.
[0011] In one embodiment of the present invention, the uniform mixing method is selected from one or more of dry ball milling, wet ball milling and high-speed dispersion.
[0012] In one embodiment of the present invention, the particle size D90 of the wet ball-milled material is less than 1 μm; And / or, the drying method is selected from one or more of fluidized bed drying, spray drying and tray drying.
[0013] In one embodiment of the present invention, the sintering is carried out under a protective atmosphere, with the temperature being increased to 700°C-850°C at a heating rate of 1°C / min-5°C / min, and the temperature being kept for 4h-24h.
[0014] In one embodiment of the present invention, the protective atmosphere is selected from nitrogen atmosphere and / or argon atmosphere.
[0015] In one embodiment of the present invention, the cooling method is selected from active cooling and / or natural cooling.
[0016] In one embodiment of the present invention, the pulverizing method is selected from one or more of mechanical pulverizing, air flow mill pulverizing and disc pulverizing.
[0017] The third object of the present invention is to provide an application of the alkaline earth metal ion-doped titanium-based phosphate composite material or the alkaline earth metal ion-doped titanium-based phosphate composite material prepared by the method in a sodium ion battery.
[0018] The technical solution of the present invention has the following advantages over the prior art: The alkaline earth metal ion-doped titanium-based phosphate composite material of the present invention effectively stabilizes the lattice structure through the doping of alkaline earth metal ions, avoids the exchange of K-Na ions, and thus significantly improves the cycle stability and service life of the battery. Compared with potassium ions, alkaline earth metal ions have a slightly larger electronegativity, and their attraction to anionic groups is stronger. When forming chemical bonds, the covalent characteristics of alkaline earth metal ions are more obvious. This strong bonding can stabilize the chemical bond network in the material, enhance the overall stability of the material, and reduce the structural damage and performance degradation caused by the breaking of chemical bonds during the charge and discharge process.
[0019] The preparation method of the present invention realizes effective doping of alkaline earth metal ions by optimizing the type and doping amount of alkaline earth metal ions and process parameters, which can effectively reduce the Fermi level, improve the electronic conductivity and ionic conductivity of titanium-based phosphate materials, thereby greatly improving the life and reversible capacity of sodium ion batteries, making the energy transmission of the battery more efficient during the charging and discharging process, reducing the internal resistance, and improving the power performance of the battery. In addition, the outermost electron configuration of the alkaline earth metal ion is ns², with two units of positive charge, and its charge density is greater than that of the alkali metal ion. In the material, the larger charge density enables the alkaline earth metal ions to more strongly attract the surrounding electrons, thereby having a more significant impact on the electronic structure of the material, which can effectively adjust the Fermi level of the material, change the band structure, and then optimize the electrical properties of the material, such as improving the conductivity and carrier mobility of the material.
[0020] The preparation method of the present invention is highly operable and easy to achieve mass production, which is beneficial to reducing production costs and promoting the large-scale commercial application of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein: Figure 1 XRD spectra of the alkaline earth metal ion-doped titanium-based phosphate composite material of Example 1 and Comparative Example 1 in Test Example 1 of the present invention; Figure 2 This is a charge and discharge curve diagram of a battery made of the alkaline earth metal ion-doped titanium-based phosphate composite material of Example 1 in Test Example 2 of the present invention at a 1C rate. DETAILED DESCRIPTION
[0022] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.
[0023] In the present invention, unless otherwise explained, technical and scientific terms used in the present invention have the same meanings as commonly understood by those skilled in the art to which the present invention belongs.
[0024] In the present invention, unless otherwise stated, the term "and / or" used in the present invention includes any and all combinations of one or more of the associated listed items.
[0025] In the present invention, unless otherwise stated, the experimental methods used in the embodiments of the present invention are conventional methods unless otherwise stated, and the materials, reagents, etc. used are all commercially available unless otherwise stated. Example 1
[0026] The alkaline earth metal ion-doped titanium-based phosphate composite material and the preparation method thereof of the present invention specifically comprise the following steps: S1, potassium dihydrogen phosphate as K source and P source, calcium carbonate as doped alkaline earth metal source, titanium dioxide as Ti source, acetylene black as carbon source material, these raw materials are 0.9 Ca 0.05 TiOPO4 / C(K 0.9 Ca 0.05 TiOPO4 and C (mass ratio of 0.95:0.05) were mixed, and then deionized water was added to make the mixture uniform, and the solid content was 40wt%, and a mixture with a particle size D90 of about 0.9μm was obtained; S2, spray drying the mixture to obtain a precursor powder with a particle size D50 of about 6.8 μm; S3. The precursor powder is placed in a sintering furnace in a nitrogen atmosphere for sintering, the temperature is increased to 750°C at a heating rate of 2.5°C / min, and the temperature is kept for 10 hours. The material after natural cooling is mechanically crushed to obtain an alkaline earth metal ion-doped titanium-based phosphate composite material. Example 2
[0027] The alkaline earth metal ion-doped titanium-based phosphate composite material and the preparation method thereof of the present invention specifically comprise the following steps: S1, potassium dihydrogen phosphate as K source and P source, barium carbonate as doped alkaline earth metal source, titanium dioxide as Ti source, acetylene black as carbon source material, these raw materials are 0.9 Ba0.05 TiOPO4 / C(K 0.9 Ba 0.05 TiOPO4 and C are mixed in a mass ratio of 0.9:0.1, and then deionized water is added to make the mixture uniformly ball-milled, with a solid content of 40wt%, to obtain a mixture with a particle size D90 of about 0.85μm; S2, spray drying the mixture to obtain a precursor powder with a particle size D50 of about 6.8 μm; S3. The precursor powder is placed in a sintering kiln in a nitrogen atmosphere for sintering, the temperature is increased to 750°C at a heating rate of 5°C / min, and the temperature is kept for 10 hours. The material after natural cooling is mechanically crushed to obtain an alkaline earth metal ion-doped titanium-based phosphate composite material. Example 3
[0028] The alkaline earth metal ion-doped titanium-based phosphate composite material and the preparation method thereof of the present invention specifically comprise the following steps: S1, potassium dihydrogen phosphate as K source and P source, magnesium carbonate as doped alkaline earth metal source, titanium dioxide as Ti source, acetylene black as carbon source material, these raw materials are 0.9 Mg 0.05 TiOPO4 / C(K 0.9 Mg 0.05 TiOPO4 and C are mixed in a mass ratio of 0.98:0.02, and then deionized water is added to make the mixture uniformly ball-milled, with a solid content of 40wt%, to obtain a mixture with a particle size D90 of about 0.95μm; S2, spray drying the mixture to obtain a precursor powder with a particle size D50 of about 6.8 μm; S3. The precursor powder is placed in a sintering kiln in a nitrogen atmosphere for sintering, the temperature is increased to 750°C at a heating rate of 2°C / min, and the temperature is kept for 10 hours. The material after natural cooling is mechanically crushed to obtain an alkaline earth metal ion-doped titanium-based phosphate composite material. Example 4
[0029] The alkaline earth metal ion-doped titanium-based phosphate composite material and the preparation method thereof of the present invention specifically comprise the following steps: S1, potassium dihydrogen phosphate as K source and P source, calcium carbonate as doped alkaline earth metal source, titanium dioxide as Ti source, acetylene black as carbon source material, these raw materials are 0.99 Ca 0.005 TiOPO4 / C(K 0.99 Ca 0.005 TiOPO4 and C (mass ratio of 0.93:0.07) were mixed, and then deionized water was added to make the mixture uniform, and the solid content was 40wt%, and a mixture with a particle size D90 of about 0.94μm was obtained; S2, spray drying the mixture to obtain a precursor powder with a particle size D50 of about 6.8 μm; S3. The precursor powder is placed in a sintering kiln in a nitrogen atmosphere for sintering, the temperature is increased to 750°C at a heating rate of 3°C / min, and the temperature is kept for 10 hours. The material after natural cooling is mechanically crushed to obtain an alkaline earth metal ion-doped titanium-based phosphate composite material. Example 5
[0030] The alkaline earth metal ion-doped titanium-based phosphate composite material and the preparation method thereof of the present invention specifically comprise the following steps: S1, potassium dihydrogen phosphate as K source and P source, calcium carbonate as doped alkaline earth metal source, titanium dioxide as Ti source, acetylene black as carbon source material, these raw materials are 0.8 Ca 0.1 TiOPO4 / C(K 0.8 Ca 0.1 TiOPO4 and C are mixed in a mass ratio of 0.8:0.2, and then deionized water is added to make the mixture uniformly ball-milled, with a solid content of 40wt%, to obtain a mixture with a particle size D90 of about 0.87μm; S2, spray drying the mixture to obtain a precursor powder with a particle size D50 of about 6.8 μm; S3. The precursor powder is placed in a sintering kiln in a nitrogen atmosphere for sintering, the temperature is increased to 750°C at a heating rate of 4°C / min, and the temperature is kept for 10 hours. The material after natural cooling is mechanically crushed to obtain an alkaline earth metal ion-doped titanium-based phosphate composite material. Comparative Example 1
[0031] The method is basically the same as Example 1, except that calcium doping is not performed, and specifically includes the following steps: S1. Potassium dihydrogen phosphate is used as the K source and P source, titanium dioxide is used as the Ti source, and acetylene black is selected as the carbon source material. These raw materials are mixed according to KTiOPO4 / C (the mass ratio of KTiOPO4 and C is 0.7:0.3), and then deionized water is added for ball milling. The solid content is 40wt%, and a mixture with a particle size D90 of about 0.9μm is obtained; S2, spray drying the mixture to obtain a precursor powder with a particle size D50 of about 6.8 μm; S3. The precursor powder is placed in a sintering kiln in a nitrogen atmosphere for sintering, the temperature is increased to 750°C at a heating rate of 3°C / min, and the temperature is kept for 10 hours. The material after natural cooling is mechanically crushed to obtain an alkaline earth metal ion-doped titanium-based phosphate composite material. Comparative Example 2
[0032] The method is basically the same as Example 1, except that the dosage of potassium dihydrogen phosphate and calcium carbonate is used, and specifically comprises the following steps: S1, potassium dihydrogen phosphate as K source and P source, calcium carbonate as doped alkaline earth metal source, titanium dioxide as Ti source, acetylene black as carbon source material, these raw materials are 0.6 Ca 0.2 TiOPO4 / C(K 0.6 Ca 0.2 TiOPO4 and C are mixed in a mass ratio of 0.8:0.2, and then deionized water is added to make the mixture uniformly ball-milled, with a solid content of 40wt%, to obtain a mixture with a particle size D90 of about 0.92μm; S2, spray drying the mixture to obtain a precursor powder with a particle size D50 of about 6.8 μm; S3. The precursor powder is placed in a sintering kiln in a nitrogen atmosphere for sintering, the temperature is increased to 750°C at a heating rate of 3°C / min, and the temperature is kept for 10 hours. The material after natural cooling is mechanically crushed to obtain an alkaline earth metal ion-doped titanium-based phosphate composite material. Comparative Example 3
[0033] The method is basically the same as Example 1, except that calcium carbonate is replaced with manganese carbonate, and specifically comprises the following steps: S1, potassium dihydrogen phosphate as K source and P source, manganese carbonate as doped alkaline earth metal source, titanium dioxide as Ti source, acetylene black as carbon source material, these raw materials are 0.9 Mn 0.05 TiOPO4 / C(K 0.9 Mn 0.05 TiOPO4 and C (mass ratio of 0.95:0.05) were mixed, and then deionized water was added to make the mixture uniform, and the solid content was 40wt%, and a mixture with a particle size D90 of about 0.9μm was obtained; S2, spray drying the mixture to obtain a precursor powder with a particle size D50 of about 6.8 μm; S3. The precursor powder is placed in a sintering furnace in a nitrogen atmosphere for sintering, the temperature is increased to 750°C at a heating rate of 2.5°C / min, and the temperature is kept for 10 hours. The material after natural cooling is mechanically crushed to obtain an alkaline earth metal ion-doped titanium-based phosphate composite material. Comparative Example 4
[0034] The method is basically the same as Example 1, except that the particle size after ball milling is different, and specifically comprises the following steps: S1, potassium dihydrogen phosphate as K source and P source, calcium carbonate as doped alkaline earth metal source, titanium dioxide as Ti source, acetylene black as carbon source material, these raw materials are 0.9 Ca 0.05TiOPO4 / C(K 0.9 Ca 0.05 TiOPO4 and C are mixed in a mass ratio of 0.95:0.05, and then deionized water is added to make the mixture uniformly ball-milled, with a solid content of 40wt%, to obtain a mixture with a particle size D90 of about 2μm; S2, spray drying the mixture to obtain a precursor powder with a particle size D50 of about 6.8 μm; S3. The precursor powder is placed in a sintering furnace in a nitrogen atmosphere for sintering, the temperature is increased to 750°C at a heating rate of 2.5°C / min, and the temperature is kept for 10 hours. The material after natural cooling is mechanically crushed to obtain an alkaline earth metal ion-doped titanium-based phosphate composite material. Comparative Example 5
[0035] The method is basically the same as Example 1, except that the particle size after ball milling is different, and specifically comprises the following steps: S1, potassium dihydrogen phosphate as K source and P source, calcium carbonate as doped alkaline earth metal source, titanium dioxide as Ti source, acetylene black as carbon source material, these raw materials are 0.9 Ca 0.05 TiOPO4 / C(K 0.9 Ca 0.05 TiOPO4 and C (mass ratio of 0.95:0.05) were mixed, and then deionized water was added to make the mixture uniform, and the solid content was 40wt%, and a mixture with a particle size D90 of about 0.9μm was obtained; S2, spray drying the mixture to obtain a precursor powder with a particle size D50 of about 6.8 μm; S3. The precursor powder is placed in a sintering kiln in a nitrogen atmosphere for sintering, the temperature is increased to 750°C at a heating rate of 8°C / min, and the temperature is kept for 10 hours. The material after natural cooling is mechanically crushed to obtain an alkaline earth metal ion-doped titanium-based phosphate composite material. Test Example 1
[0036] XRD characterization was performed on the alkaline earth metal ion-doped titanium-based phosphate composite materials of Example 1 and Comparative Example 1. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that the XRD diffraction peaks of the two are consistent, which shows that within a certain doping range, the lattice structure of the material will not change. Test Example 2
[0037] (1) Testing the powder resistivity R (Ω·cm) of the titanium-based phosphate composite materials of Examples 1-5 and Comparative Examples 1-5: The powder resistivity of the titanium-based phosphate composite materials was measured using an ST2742C automatic powder resistivity tester. Under the same carbon content, the electronic conductivity of the titanium-based phosphate composite materials can be directly reflected. The curve between pressure (MPa) and resistivity (Ω·cm) was recorded, and the resistivity at a pressure of 60 MPa was used as a comparison between different samples.
[0038] (2) Batteries were manufactured and their performance tested based on the titanium-based phosphate composite materials of Examples 1-5 and Comparative Examples 1-5: Battery Assembly: Negative electrode sheet: titanium-based phosphate composite material, acetylene black as conductive agent, polyvinylidene fluoride (PVDF) as adhesive, and 6μm aluminum foil as negative electrode current collector; titanium-based phosphate composite material, conductive agent and adhesive are mixed in a mass ratio of 8:1:1, and N-methylpyrrolidone is added and stirred into a uniform and stable negative electrode slurry, and then the negative electrode slurry is evenly coated on the surface of the negative electrode current collector, and 200μm scraper coating is performed, and the negative electrode sheet is obtained after drying and cold pressing. The mass load of the titanium-based phosphate composite material is about 2.5mg / cm 2 .
[0039] Counter electrode: Sodium metal sheet.
[0040] Isolation film: The base film of the isolation film is a polyethylene film with a thickness of 9μm.
[0041] Electrolyte: Sodium hexafluorophosphate was dissolved in polycarbonate to prepare an electrolyte with a concentration of 1 mol / L.
[0042] Assembly of sodium ion battery: Arrange the negative electrode sheet, separator, counter electrode and separator in sequence, and use winding as the assembly method.
[0043] Performance test: The assembled sodium-ion battery is tested for specific capacity, cycle stability, etc.: (1) Specific capacity (mAh / g) test: The specific capacity of the titanium-based phosphate composite material was tested in the voltage range of 0-3V; (2) Cycle stability (%) test: On a battery cycle test device, set the discharge voltage range to 0.5V-3V, and perform a 5C charge and 5C discharge cycle test on the sodium ion battery at room temperature, and record the number of cycles at which the capacity tends to stabilize. At the same time, record the initial capacity Qinitial and the capacity after 8000 cycles Q8000 cycles, and calculate the capacity retention rate of each battery after 8000 cycles = (Q8000 cycles / Qinitial) × 100%.
[0044] Table 1 and Figure 2 The following are the relevant performance parameters finally measured: Table 1
[0045] From Table 1 and Figure 2 It can be seen that the specific capacity and cycle stability of titanium-based phosphate composites are improved to varying degrees by adjusting the type and doping amount of per-alkaline earth metal ions and optimizing the process parameters.
[0046] It can be seen from Examples 1-3 and Comparative Example 1 that the specific capacity, powder resistivity and cycle stability of the titanium-based phosphate composite material obtained by doping with different alkaline earth metals (at a certain doping content) are not much different. This is because the electron cloud structures of different alkaline earth metal ions are similar, and they can enter the lattice after doping. When the alkaline earth metal ions with strong electronegativity form ligands with oxygen ions and phosphate ions, their electron cloud structures enable them to form strong chemical bonds with the ligands. This strong bonding can stabilize the chemical bond network in the material, enhance the overall stability of the material, and reduce the structural damage and performance degradation caused by chemical bond breakage during the charge and discharge process. Adjusting the crystal structure of the titanium-based phosphate composite material can increase the phase stability and ensure the long-term cycle stability of the titanium-based phosphate composite material. At the same time, alkaline earth metal doping can effectively adjust the Fermi level of the material, change the band structure, increase the mobility of oxygen ions and the conductivity of grain boundary oxygen ions, and thus improve the overall conductivity of the material.
[0047] It can be seen from Examples 1, 4-5 and Comparative Examples 1-2 that when the doping amount is between 0.001-0.1, the specific capacity increases slightly with the increase of the doping content. This is because as the doping amount of alkaline earth metal ions increases, the attraction to anion groups such as oxygen ions and phosphate ions increases, and the energy band gap of the material decreases slightly, causing an increase in specific capacity. At the same time, the lattice structure is more stable and the capacity retention rate is also improved. However, when the alkaline earth metal doping amount is less than 0.001 (Comparative Example 1), although the specific capacity of the material does not decrease much, due to the lack of strong coupling of alkaline earth ions, the powder conductivity and cycle stability are greatly increased and decreased respectively. When the alkaline earth metal doping amount is higher than 0.1 (Comparative Example 2), because the amount of alkaline earth metal doped is too much, the lattice distortion is caused, thereby changing the ion diffusion channel of the original material, resulting in a sharp decrease in the specific capacity and cycle stability of the material.
[0048] It can be seen from Example 1 and Comparative Example 3 that when manganese ions are used for doping, the specific capacity of the obtained material is very low. This is mainly because the electronic configuration of manganese ions is relatively complex, the d orbital has a specific extension direction and shape in space, and its electron cloud distribution is in a complex shape such as a petal shape, which makes the manganese ions have strong directionality and spatial selectivity when forming chemical bonds, and cannot be well combined with anion groups such as oxygen ions and phosphate ions, making it difficult to generate materials with the desired crystal structure.
[0049] It can be seen from Example 1 and Comparative Example 4 that when the particle size D90 of the slurry obtained by wet ball milling is greater than 1 μm, due to the relatively large particle size of the raw material, the distance of the material transmission process during the sintering process increases, resulting in an increase in the primary particle size of the material and the easy generation of impurities. The appearance of excessive particle size and impurities is not conducive to the conduction of ions inside the material and the stability of the lattice structure. During the charge and discharge process, it will hinder the normal deintercalation of ions, thereby reducing the specific capacity of the obtained titanium-based phosphate composite material, and also seriously affecting the cyclic stability of the material, causing the material to rapidly decay after multiple charge and discharge.
[0050] It can be seen from Example 1 and Comparative Example 5 that when the heating rate is too fast during the sintering process, the phosphorus source does not have time to decompose. As a key component in the formation of titanium-based phosphate composite materials, insufficient decomposition of the phosphorus source will lead to an imbalance in the proportion of the material components and an inability to form an ideal crystal structure. The incompletely decomposed phosphorus source may exist in the material in the form of an impurity phase, affecting the purity of the material. This will not only interfere with the transmission channel of ions inside the material, making it difficult for ions to migrate in the lattice and reducing the specific capacity of the material, but will also destroy the stability of the lattice, causing the lattice to be more susceptible to irreversible deformation during the charge and discharge process, seriously damaging the cyclic stability of the material.
[0051] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. An alkaline earth metal ion-doped titanium-based phosphate composite material, characterized in that: The chemical formula of the alkaline earth metal ion-doped titanium-based phosphate composite material is K x M y TiOPO4 / C, M is selected from one or more of beryllium, magnesium, calcium, strontium and barium, 0.8≤x≤0.95, 0.001≤y≤0.1, and the values of x and y satisfy the charge balance of the chemical formula.
2. The alkaline earth metal ion-doped titanium-based phosphate composite material according to claim 1, characterized in that: The M is selected from magnesium and / or calcium.
3. The alkaline earth metal ion-doped titanium-based phosphate composite material according to claim 1, characterized in that: The chemical formula of the alkaline earth metal ion-doped titanium-based phosphate composite material is K 0.9 Ca 0.05 TiOPO4 and / or K 0.9 Mg 0.05 TiOPO4.
4. The alkaline earth metal ion-doped titanium-based phosphate composite material according to claim 1, characterized in that: The K x M y The mass ratio of TiOPO4 and C is (0.7-0.99):(0.01-0.3).
5. The method for preparing the alkaline earth metal ion-doped titanium-based phosphate composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The K source, M source, Ti source, P source and carbon source are uniformly mixed by wet ball milling, and the alkaline earth metal ion-doped titanium-based phosphate composite material is obtained through drying, sintering, cooling and crushing.
6. The method for preparing the alkaline earth metal ion-doped titanium-based phosphate composite material according to claim 5, characterized in that: The K source is selected from one or more of potassium hydroxide, potassium carbonate, potassium sulfate, potassium dihydrogen phosphate and potassium acetate; And / or, the M source is selected from one or more of a beryllium source, a magnesium source, a calcium source, a strontium source and a barium source; and / or, the Ti source is selected from one or more of titanyl sulfate, titanium dioxide, tetrabutyl titanate and titanium tetrachloride; And / or, the P source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphorus pentoxide and potassium dihydrogen phosphate; And / or, the carbon source is selected from one or more of acetylene black, graphite, conductive carbon black, sucrose and glucose.
7. The method for preparing the alkaline earth metal ion-doped titanium-based phosphate composite material according to claim 5, characterized in that: The particle size D90 of the material after wet ball milling is less than 1 μm; And / or, the drying method is selected from one or more of fluidized bed drying, spray drying and tray drying.
8. The method for preparing the alkaline earth metal ion-doped titanium-based phosphate composite material according to claim 5, characterized in that: The sintering is carried out under a protective atmosphere, with the temperature being raised to 700° C.-850° C. at a heating rate of 1° C. / min-5° C. / min, and the temperature being kept for 4h-24h.
9. The method for preparing the alkaline earth metal ion-doped titanium-based phosphate composite material according to claim 8, characterized in that: The protective atmosphere is selected from nitrogen atmosphere and / or argon atmosphere.
10. Use of the alkaline earth metal ion-doped titanium-based phosphate composite material according to any one of claims 1 to 4 or the alkaline earth metal ion-doped titanium-based phosphate composite material prepared by the method according to any one of claims 5 to 9 in a sodium ion battery.
Citation Information
Patent Citations
Method of liquid-phase synthesizing KTP (Potassium Titanyl Phosphate) crystal precursor
CN103590093A
Synthesis and application of sodium ion battery electrode material KTiOPO4
CN108448095A
Potassium titanyl phosphate negative electrode material for potassium ion secondary battery
CN108878876A
One-dimensional carbon-coated pi-Ti2O (PO4) 2 material as well as preparation method and application thereof
CN116314665A
Chlorine-containing titanium magnesium phosphate solid electrolyte as well as preparation and application thereof
CN117410551A